Is Articaine More Potent than Mepivacaine for Use in Oral Surgery? - Giath Gazal (Stilus Optimus, 2018)
Objectives: To investigate the potency and speed of action of 4% articaine and 2% mepivacaine for maxillary teeth extractions. Material and Methods: Ninety-four patients, aged between 16 to 70 years old, were recruited in this study. Two regimens were randomly administered over one visit. Patients of treatment group 1 received mepivacaine 2% with 1:100,000 adrenaline, whereas treatment group 2 - articaine 4% with 1:100,000 adrenaline. The onset time of pulp anaesthesia for maxillary teeth indicated for extraction was determined by electronic pulp testing. At any point of trial (10 minutes), the anesthetized tooth becomes unresponsive for maximal pulp stimulation (64 reading), the extraction was carried out. Results: In this study, 85 patients had successful local anaesthetic followed by extraction within the study duration time (10 min). However, 5 patients had failed dental extraction (4 in mepivacaine group and 1 in articaine group). Patients in the articaine buccal infiltration group recorded faster onset time of action regarding anaesthesia and teeth extraction than patients in mepivacaine buccal infiltration group (P = 0.03). Conclusions: Articaine is an effective anaesthetic with a rapid onset, comparable to mepivacaine in infiltrative techniques used for maxillary teeth extraction. However, articaine has clinically achieved faster dental anaesthesia and earlier teeth extraction than mepivacaine. So, articaine can be the local anaesthetic of first choice in oral surgery.